2013
DOI: 10.4209/aaqr.2012.03.0061
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Short-Term Emission Rates of Particles in the “Personal Cloud” with Different Clothes and Activity Intensities in a Sealed Chamber

Abstract: A series of measurements were conducted to determine the short-term emission rates of particles in the "personal cloud" (i.e., particle emission from a clothed human body) in a sealed chamber. By recording the concentration of particles of different sizes during a period of time in the chamber, curves monitoring the evolution of particle concentration caused by emissions from a clothed human body were obtained. Based on the measured evolution of particle concentrations and deposition rates, the emission rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 51 publications
2
66
0
1
Order By: Relevance
“…This may be explained by active indoor sources, activities/movements of the occupants and reduced ventilation rates as a result of closed doors and windows, so causing accumulation. Among the indoor sources of organic compounds, submicrometer fragments of paper, skin debris, clothing fibres, cleaning products and waxes may be considered (Schneider, 2008;Weschler, 2012;You et al, 2013). Air exchange rates below 1 h -1 , such as those usually registered in Portuguese classrooms, including the school focused in this study , have been reported to contribute to the enrichment of particulate pollution in indoor environments (Abt et al, 2000;RojasBracho et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…This may be explained by active indoor sources, activities/movements of the occupants and reduced ventilation rates as a result of closed doors and windows, so causing accumulation. Among the indoor sources of organic compounds, submicrometer fragments of paper, skin debris, clothing fibres, cleaning products and waxes may be considered (Schneider, 2008;Weschler, 2012;You et al, 2013). Air exchange rates below 1 h -1 , such as those usually registered in Portuguese classrooms, including the school focused in this study , have been reported to contribute to the enrichment of particulate pollution in indoor environments (Abt et al, 2000;RojasBracho et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Only a few studies have quantified human emissions of total and biological airborne particles with a high temporal and particlesize resolution. [13][14][15] You et al 13 identified a positive correlation between the vigour of human activity and the emission rates of total airborne particles. Bhangar et al 14,15 used a laserinduced fluorescence-based ultraviolet aerodynamic particle sizer (UV-APS) to quantify human emission rates of fluorescent biological aerosol particles and reported that human skin and clothes are important sources indoors.…”
Section: Accepted Articlementioning
confidence: 99%
“…Indoor exposure to particles is especially important, because people spend most of their time indoors (Klepeis et al 2001). The sources of indoor particles include ambient particles (Chen and Zhao 2011), cigarette smoking (Spengler et al 1981), cooking (Ozkaynak et al 1996), human body emission (You et al 2013), human exhalation (Nicas et al 2005), and ozone reactions (Weschler 2006). Many studies assume that particle concentrations are uniform indoors, which may lead to significant errors in personal exposure assessments (Li et al 2005).…”
Section: Introductionmentioning
confidence: 99%